Dilema Praktik Kantor Akuntan Publik: Pertautan antara Keberlangsungan Hidup dengan Kualitas Audit - Anggraini, Anggi Ratna (Jurnal Ekonomi Modernisasi, 2018)
This research focuses on the dilemma of small Public Accounting Firms in maintaining their survival, but still maintaining their audit quality. This research is qualitative research with interpretive paradigm and the case study method. This study shows how Public Accounting Firm X faces a dilemma situation when auditing small clients with low fees, while maintaining their audit quality. Public Accounting Firm X in its survival growth strategy uses a "zebra", a "radar" and a business diamond strategy. Public Accounting Firm X itself has a dilemma when faced with a small client who can only pay a low fee for audit services, if using the indicator minimum hourly charge-out rates determined by IAPI, then the audit fee cannot be applied on the client. In the end, the audit procedures carried out must be adequate to maintain audit quality, where Public Accounting Firm X uses Excel based Standard Working Paper during audits and cuts the leveling level. Regulations that accommodate more smaller clients in the area are needed related to audit services.